Penerapan Metode Pengajaran Bahasa Situasional (PBS) Untuk Meningkatkan Penguasaan Kosakata Bahasa Inggris - Arik Aryawathi, Si Luh Putu; Sutjiati Beratha, Ni Luh; Dhanawaty, Ni Made (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2021)
This article aims to describe the vocabulary mastery of training participants at the Dhyana Pura Tourism Education and Training Center, PPLP, in the front office before and after the implementation of the Situational Language Teaching (SLT) method. This article used a mixture of quantitative and qualitative methods, especially concurrent mixed methods with experimental design in the form of Intact - Group Comparison. The sample selection used nonprobability sampling technique, namely purposive sampling. The quantitative analysis results show that in the pretest phase, the mean vocabulary mastery of the training participants at PPLP before the implementation of the SLT method only reached the E predicate (failed) with a value of 27 from a maximum value of 100 with a success rate of 26.80% for the experimental class and a score of 25 with a success rate of 24.50% for the control class. After the treatment, the results of the posttest proved that there was an increase in the average vocabulary mastery of training participants in the experimental class by 58.63% with a posttest mean score of 85 (85.43%), predicate A (very good). Whereas in the control class that was not subject to action, the increase was very small, only 15.97% with a mean posttest score of 40 (40.47%), predicate D (less). The SLT method is very effective and efficient to assist the learning process in the classroom because training participants can be trained to find, place and use vocabulary according to the context practically through the conversations that have been made.